A Model For Estimating The Costs Of Injury Accidents In Underground Coal Mining With Application To 1974 Injury Experience Data - Daniel G. DiCanio (Society for Mining, Metallurgy & Exploration, 1977)
Investigation of the costs of industrial accidents dates back to the 1920s. The Bureau of Mines was one of the pioneers in accident cost investigation with numerous studies published between 1928 and 1933. The bulk of these early investigations dealt only with costs which appeared as payouts on company books; that is, the direct cost of insurance premiums and the costs of medical expenses which resulted from industrial accidents. These early investigations, especially the Bureau's study of accident costs in Pennsylvania and Indiana coal mines provided the first real evidence that promotion of industrial safety pays back in dollars as well as in human life and wellbeing. In the 30s and 40s, investigations began to accumulate evidence that industrial accidents impacted more than just the direct operating expenses of a company (i.e., higher insurance premiums). The work of Heinrich pioneered these investigations, and produced strong evidence that the un¬insured costs of accidents far outweighed those costs covered by insurance. Heinrich developed and published a ratio of insured to uninsured costs of 1.4. Despite his cautionary statements about blanket application of this ratio it is used even today to estimate total costs of accidents. Simonds, in the late 40s and early 50s, extended the definitions of uninsured or indirect accident costs and developed what is now regarded as the principal method for estimating the total economic impact of industrial accidents. Simonds' method served as the basis for development of the logic of the Accident Cost Indicator Model (ACIM). However, several departures from Simonds' method were made to satisfy certain requirements imposed by the Bureau of Mines, and because information gathered during the course of our investigation justified a departure. These departures are noted in the discussion which follows.